Animal performance and biochemical parameters are sex-dependent in peripubertal rats exposed to deoxynivalenol. (December 2022) - Gerez, J.R.; Verri, W.A.; Hohmann, M.S.; Flaiban, K.M.C.; Hasuda, A.L.; Gloria, E.M.; Bracarense, A.P.R.L.
Abstract: Deoxynivalenol (DON), a mycotoxin produced mainly by Fusarium graminearum and F. culmorum commonly contaminates food commodities across the globe. Due to this, exposure to DON might pose potential health hazards to humans and animals. Biological factors like sex and age can influence the toxicity of DON. However, in toxicological studies involving DON, the sex and age-dependent response has been often overlooked. Thereby, the objective of this study was to evaluate if sex differences are evident in DON's systemic effects in peripubertal rats. Juvenile animals (n = 24) with 28 days postnatal day were randomly assigned to two experimental groups: Control group (n = 12, 6 females and 6 males, mycotoxin-free diet) and DON group (n = 12, 6 females and 6 males, diet containing 10 mg DON/kg of feed). During 28 days of treatment, the animals were weighed weekly and body weight gain and food intake were calculated for each week. After the experimental period, blood samples, intestine, liver, and kidney were collected and destined for biochemical, hematological, histopathological, and oxidative stress analyses. Greater anorectic responses were seen in males, while only females showed increased levels of creatinine and triglycerides. Regardless of sex, DON induces an increased number of white blood cells, particularly lymphocytes and a significant reduction in the levels of hemoglobin, hematocrit, mean corpuscular hemoglobin, and neutrophils. In males and females fed a DON-contaminated diet, histological lesions were observed in the intestine, liver, and kidney. Ingestion of DON induced a significant increase in the antioxidant potential in the intestine, liver, and kidney. However, this effect was not able to prevent oxidative stress in the renal tissue. Taken together, our results showed a sex-related response in food intake, weight gain, and biochemical parameters in rats exposed to DON during the juvenile and peripubertal periods. In addition, we have verified that oxidative stress is an important mechanism in the nephrotoxicity of DON. Graphical abstract: Image 1 Highlights: DON induces a sex-related response in food intake, weight gain, and biochemical parameters in peripubertal rats. Hematological, histological, and oxidative stress response to DON is not sex-dependent in peripubertal rats. DON nephrotoxicity is modulated by an oxidative stress response.